192k views
3 votes
Solve the following equation. –4y + 8 = 4(2y – 2) – 2(–16 + 8y) A. y = –4 B. y = 4 C. y = –2 D. y = –6 I need Help I am utterly useless.

User Lmz
by
5.1k points

1 Answer

7 votes
The answer is B. (y = 4)


Further explanation:

–4y + 8 = 4(2y – 2) – 2(–16 + 8y)
= -4y + 8 = 4 * (2y -2) - 2 * (-16 + 8y)
= -4y + 8 = ( 4 * 2y - 4 *2 ) - (2 * -16 - 2 * 8y )
= -4y + 8 = 8y - 8 - ( -32 - 16y)
= -4y + 8 = 8y - 8 + 32 + 16y
Move y’s to the left & numbers to the right
= -4y - 8y - 16y = -8 + 32 - 8
= 12y - 16y = -16 + 32
Y = 16 / 28
Y = 4 = (B choice)
User Zhigang
by
5.1k points